Drug–Food Interactions Between Iron Supplements and Antacids: An In Vitro Investigation - منهل نبيل يوسف (Latakia University Journal -Medical Sciences Series, 2023)
This in vitro study evaluated the effect of antacids on the bioavailability of iron from two commonly used oral supplements—ferrous sulfate and ferrous gluconate. These supplements were combined with different classes of antacids, including proton pump inhibitors (omeprazole) and hydroxide-based antacids (magnesium and aluminum hydroxides), across a range of physiologically relevant pH levels (1.5–7.5). Using the Ferrozine assay, a significant reduction in soluble Fe²⁺ concentrations was observed with increasing pH, especially above pH 5.0. The presence of magnesium and aluminum hydroxide led to sharp declines in iron solubility due to complex formation or precipitation, while omeprazole showed a milder effect. Statistical analysis confirmed the significance of these interactions (p < 0.05 to p < 0.001). These findings emphasize the importance of dosing separation and appropriate antacid selection in clinical practice to prevent impaired iron absorption.